THE EFFECT OF SERVICE QUALITY AND PRODUCT QUALITY ON CONSUMER PURCHASING DECISION OF READY MIX CONCRETE AT PT DUTA BETON SEJATI MEDAN - M. Agung Anggoro (UNIVERSITAS SARI MUTIARA INDONESIA, 2018)
Consumers often complained about the services provided by employees because the service was not compatible with consumer expectations. These complaints are often not responded by employees well. It was predicted that management paid less attention to the concrete production process (at the field site or quality control) so that concrete results were less in line with consumer expectations. Concrete production targets are not reached or decreased in July and September in 2016. The objective of the research is to test and analyze the effect of service quality and product quality on consumer purchase decision of ready mix concrete at PT. Duta Beton Sejati Medan The approach of this research is quantitative. The population of this study were 150 consumers. The sample of this study were 110 respondents in the company and 30 respondents were used to test the validity. Data analysis used was a multiple linear regression and assumption test of classical used were normality, multicolinearity and heterokedastisitas. The results showed that the quality of service has a positive and significant impact on consumer purchasing decision of ready mix concrete at PT. Duta Beton Sejati Medan. Product quality have positive and significant effect to consumer purchasing decision of ready mix concrete at PT. Duta Beton Sejati Medan. Quality of service and product quality have an effect and significant to consumer purchasing decision of ready mix concrete at PT. Duta Beton Sejati Medan. Keywords: Quality of Service, Product Quality, Purchase Decision